Translation and Replication of Human Rhinovirus Type 14 and Mengovirus in Xenopus Oocytes - Gamarnik, Andrea V. (American Society for Microbiology, 2000)
We have previously shown that Xenopus oocytes require coinjection of both poliovirus RNA and HeLa cell extracts to support a complete cycle of viral replication yielding high levels of infectious viral particles. This novel system provides a tool for identifying host factors and for biochemically dissect individual steps that lead to virus production. Here we demonstrate that Xenopus oocytes are able to support replication of other picornaviruses such as human rhinovirus 14 and mengovirus. Unlike poliovirus, microinjection of mengovirus RNA yields high viral titers (about 10(7) PFU/oocyte) without the need for coinjection of additional cell extracts. In contrast, formation of infectious rhinovirus particles requires coinjection of human cell extracts. We found that one of these human factors is required for efficient rhinovirus translation. Our findings uncover differences in the host factor requirements among members of the picornavirus family and provide the means to identify the human protein(s) involved in rhinovirus production.